Mollusca Biodiversity as A Quality Bioindicator Waters in Central Lombok Gerupuk Bay Coastal Area - Berliana, Cok Gea; Candri, Dining Aidil; Ahyadi, Hilman (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Various natural resource utilization activities on the coast of Gerupuk Bay can potentially affect the quality of the aquatic environment, both biotic and abiotic, one of which is mollusc biodiversity. This study aimed to determine the relationship between the existence of Mollusca biodiversity and water quality and substrate in Gerupuk Bay. This study used a quantitative descriptive method of determining stations using the purposive sampling method based on differences in community activities at each station. Sampling was conducted at three stations, including Mollusca samples and water quality measurements: salinity, pH, temperature, and substrate. Molluscs in Gerupuk Bay found 55 species of Mollusks representing three classes, namely the Gastropoda class, with as many as 44 species incorporated in 22 Families; the Bivalve class, as many as ten species contained in 6 Families; and the Scaphopoda class, with as many as one types incorporated in 1 Family. The composition of Mollusca classes found on the Gerupuk Bay Coast is Gastropoda class at 62%, Bivalve class at 35%, and Scaphopoda class at as much as 3%. Mollusca diversity is calculated using the Shannon-Wienner diversity index (H'). The diversity index results ranged from 2.890-1.998, with moderate categories at all stations. Bioindicators of water quality using the diversity index show that stations I and III categorize the Gerupuk Bay area as lightly polluted. In contrast, at station II, it is moderately polluted.